CHALLENGES IN THE ADAPTIVE RE-USE APPROACH OF HERITAGE BUILDING AT PUBLIC UNIVERSITY IN MALAYSIA - Ani Syahirah Zainal Abidin; Nor Zalina Harun; Asyaari Muhamad (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
Historic buildings are now gaining the attention of various parties to ensure that historic buildings can be maintained in the future. In an effort to preserve historic buildings in Malaysia, various measures have been taken including the relocation of historic buildings involving several methods and types of use. However, the suitability of relocation and re-use of the building according to the suitability of the new site as well as the needs of its users is often in dispute till this day. The absence of guidelines and long-term activity plan in ensuring the continued use of historic buildings is a major factor that is often tinted by many parties in architectural and building maintenance discipline. The aim of this study is to analyse the viability of approaches and planning for heritage buildings that have undergone relocation and adaptive reuse in four public universities. The selection of subjects is in line with the recent trend, which indicates that more and more public universities have started to participate in conservation projects since the early 2000. This study is a qualitative study involving observations and interviews method of data collection which covers 7 heritage buildings at 4 public universities in Malaysia. Three adaptive approaches, namely - museums, architectural research centres, and arts and cultural centres, were found in this review. However, certain factors of building management and maintenance have been described as the greatest constraints in ensuring the building conservation remains sustainable. The study therefore suggests that a new approach to technology development and sustainability themes considerations is a significant aspect to be considered in the future.